Analysis of the quality of life of patients submitted to surgical treatment of breast cancer (Research, Society and Development, 2023)
Breast cancer, a pathology resulting from the sum of genetic and epigenetic factors and the cause of immense negative effects for the patient throughout her life context, represents the second most frequent tumor in women in Brazil. There are several therapeutic forms for breast carcinoma such as radiotherapy, chemotherapy, hormone therapy and surgical oncological treatment, among which there is total mastectomy and breast-conserving surgery, indicated according to the type of cancer and its stage. It should be noted that these surgeries can cause complications such as skin necrosis, infections, hematomas and lymphedema in the arms, in addition to psychologically affecting patients. This quantitative, descriptive and exploratory cross-sectional study aims to compare the impacts on the quality of life of women undergoing surgical treatment for breast cancer, using the BREAST-Q questionnaire, so that the impacts of the two surgical techniques can be analyzed. in the group of patients interviewed. Based on the study, it was possible to demonstrate the difference between the influences of the two surgical treatment scenarios on the patients' quality of life, showing that mastectomy has a more significant negative impact than breast-conserving surgery in all aspects addressed. It is concluded that there is a need to develop strategies to restore these women's quality of life.